Abordagens da alienação parental: proteção e/ou violência? - Márcia Amaral Montezuma (2015)
This dissertation analyzes under which legal, medical, psychological and social conceptions is parental alienation (PA) being discussed, specifically one called parental alienation syndrome (PAS), by means of wide literature review and qualitative research involving interviews with the staff of psychosocial studies, mediators and judges of the Family Court of Lafayette Forum of Belo Horizonte. The controversies regarding the concept of PAS were covered, as well as its relevance to medical diagnosis and to the treatment proposed by Gardner, just like their effects of medicalization of the behavior, in which the subjective, social, political and economical context are denied; the demand for judicialization of parental alienation, where legal regulations try to overcome deficiencies in the areas of health and education and, finally, the interference of the state in private matters, with the consequent invasion of the subject by a systemic approach at the expense of its accountability by its own way of dealing with life's experiences. It was concluded that by easing the clinical and legal approaches it is possible for the state to fulfill its function of protecting the minor in vulnerable condition, but without incurring in institutional violence. Were appointed as examples in this direction the mediation and the new law on joint custody, which together with therapeutic interventions, point to the responsibility of the individual towards his choices and acts as the best way of resolving conflicts.